2022
DOI: 10.1007/s40520-022-02236-3
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of an early warning model for predicting the acute kidney injury in elderly patients with sepsis

Abstract: Background Sepsis-induced acute kidney injury (S-AKI) is a significant complication and is associated with an increased risk of mortality, especially in elderly patients with sepsis. However, there are no reliable and robust predictive models to identify high-risk patients likely to develop S-AKI. We aimed to develop a nomogram to predict S-AKI in elderly sepsis patients and help physicians make personalized management within 24 h of admission. Methods A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Recognition of patients at high risk for renal outcomes within 24 h after ICU admission could allow providers to avoid risk factors, such as nephrotoxic drugs and radiocontrast dye. Classical theories propose that the elderly have high mortality, PRD, and RRT in sepsis patients because various factors may contribute to the decline in renal function with advancing age, encompassing the atrophy and degeneration of renal tubular epithelial cells, a thickened basement membrane, and reduced renal blood flow (13). In line with our study, previous research findings have demonstrated a substantial rise in the incidence of sepsis (58-65%) among elderly patients, with age being identified as an independent predictor of sepsis mortality (14).…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of patients at high risk for renal outcomes within 24 h after ICU admission could allow providers to avoid risk factors, such as nephrotoxic drugs and radiocontrast dye. Classical theories propose that the elderly have high mortality, PRD, and RRT in sepsis patients because various factors may contribute to the decline in renal function with advancing age, encompassing the atrophy and degeneration of renal tubular epithelial cells, a thickened basement membrane, and reduced renal blood flow (13). In line with our study, previous research findings have demonstrated a substantial rise in the incidence of sepsis (58-65%) among elderly patients, with age being identified as an independent predictor of sepsis mortality (14).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional statistical analysis has been instrumental in identifying risk factors for SA-AKI across a range of comorbidities, infections, medications, and other determinants [4,[34][35][36][37][38][39][40][41][42]. Key comorbid conditions found to significantly predict SA-AKI include hypertension, diabetes mellitus, chronic kidney disease, cardiovascular disease, liver disease, and coronary artery disease [4].…”
Section: Predictors and Mortality Of Sepsis-associated Acute Kidney I...mentioning
confidence: 99%
“…Traditional statistical approaches to predicting SA-AKI through various studies have been used [34][35][36][37][38][39][40][41][42]. These studies (Table 1) utilized well-established methods such as logistic regression analysis, least absolute shrinkage and selection operator (LASSO) regression for variable selection, and calibration plots [34][35][36][37][38][39][40][41][42].…”
Section: Prediction Model For Sepsis-associated Acute Kidney Injury B...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study identified several independent predictor variables including age, emergency ICU admission, post-surgical cases, admission diagnosis, AKI etiology, disease severity score, mechanical ventilation, use of boosters and blood outcomes such as albumin, potassium, and pH ( 8 ). In a study analyzing 30-day mortality in elderly patients with sepsis, a multivariate logistic regression-based analysis was conducted and resulted in a more accurate prediction with an AUC of 0.831 ( 9 ). Additionally, a multivariate prediction model for ICU and in-hospital death in AKI patients undergoing continuous renal replacement therapy found to be more accurate than SOFA, APACHE-II, and SAP-II scores ( 10 ).…”
Section: Introductionmentioning
confidence: 99%